The Impact of Outcome-Based Digital Assessment on Self-Regulated Learning in General Chemistry Education - HRA Mulyani; Ratini Ratini (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to investigate the impact of integrating Outcome-Based Education (OBE)-oriented digital assessments on students’ self-regulated learning (SRL) in General Chemistry courses. A quasi-experimental design was employed involving 50 undergraduate students who participated in four sessions of formative assessments delivered through digital platforms such as Quizizz and Google Forms. Each assessment item was carefully aligned with specific learning outcomes and designed to support five SRL dimensions: goal setting, time management, self-monitoring, help-seeking, and self-evaluation. Data were collected using pre- and post-intervention questionnaires and tests, and subsequently analyzed through paired sample t-tests. The results revealed a statistically significant improvement in overall SRL scores (from 64.52 to 77.84, p < 0.001), with the most notable increases observed in self-monitoring and help-seeking. These findings indicate that embedding digital formative assessments within an OBE framework can foster learners’ autonomy, metacognitive engagement, and reflective learning strategies. The study underscores the pedagogical value of aligning assessment with learning outcomes while leveraging feedback-driven digital tools to create meaningful and sustainable learning experiences in higher education, particularly in science-related disciplines